Early response to the emergence of influenza A(H7N9) virus in humans in China: the central role of prompt information sharing and public communication - Vong, Sirenda; O’Leary, Michael; Feng, Zijian (Bulletin of the World Health Organization, 2014)
In 2003, China's handling of the early stages of the epidemic of severe acute respiratory syndrome (SARS) was heavily criticized and generally considered to be suboptimal. Following the SARS outbreak, China made huge investments to improve surveillance, emergency preparedness and response capacity and strengthen public health institutions. In 2013, the return on these investments was evaluated by investigating China's early response to the emergence of avian influenza A(H7N9) virus in humans. Clusters of human infection with a novel influenza virus were detected in China - by national surveillance of pneumonia of unknown etiology - on 26 February 2013. On 31 March 2013, China notified the World Health Organization (WHO) of the first recorded human infections with A(H7N9) virus. Poultry markets - which were rapidly identified as a major source of transmission of A(H7N9) to humans - were closed down in the affected areas. Surveillance in humans and poultry was heightened and technical guidelines were quickly updated and disseminated. The health authorities collaborated with WHO in risk assessments and risk communication. New cases were reported promptly and publicly. The relevant infrastructures, surveillance systems and response capacity need to be strengthened in preparation for future emergencies caused by emerging or existing disease threats. Results of risk assessments and other data should be released promptly and publicly and such release should not jeopardize future publication of the data in scientific journals. Coordination between public health and veterinary services would be stronger during an emergency if these services had already undertaken joint preparedness planning.